Information quality, sharing and usage in farmer organizations: the case of rice value chains in Bugiri and Luwero Districts, Uganda - Hilary, R.S.; Sseguya, H.; Kibwika, P. (Informa UK Limited, 2017)
Information is the connection of all components of a value chain network, activities and operations. Information transfer depends on the level of trust and interaction in the structure of the chain’s information system. This study was conducted on information quality, sharing and usage by two OSCAs in the rice value chain in Luwero and Bugiri districts, Uganda. The methodology used involved use of semi structured interviews, check lists for focus group discussions and key informant interviews. Seven focus group interviews were conducted, with an average attendance of six members per group (42 members) in Bugiri and 42 members in Luwero district. Interviews were also conducted for 30 key informants. A total of 114 respondents were interviewed in focus group discussions and as key informants. The information was analyzed with NVIVO software. Findings indicate that information sharing, type, quality content and usage of information depended on trust. Trust was a result of regular interactions among the network actors to learn more about each other. The result was exchange of more important and valuable information within the OSCAs. However, reliability of the information from actor perspective varied, with information from government actors being the least reliable and that from the private actors being the most reliable. Feedback was also an impediment to information sharing, caused by lack of trust among some actors. We recommend that it is imperative to have feedback within and among actors to enable establish trust and genuine sharing of information to address specific information gaps.